2019
DOI: 10.3390/molecules24152772
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine: Isolation, LC–MS QTof Screening, and Anticancer Activity Study of Gloriosa superba Seeds

Abstract: Colchicine was extracted from Gloriosa superba seeds using the Super Critical Fluid (CO2) Extraction (SCFE) technology. The seeds were purified upto 99.82% using column chromatography. Colchicine affinity was further investigated for anticancer activity in six human cancer cell lines, i.e., A549, MCF-7, MDA-MB231, PANC-1, HCT116, and SiHa. Purified colchicine showed the least cell cytotoxicity and antiproliferation and caused no G2/M arrest at clinically acceptable concentrations. Mitotic arrest was observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…On the other hand, the monoterpenoid indole alkaloids vindoline and catharanthine, isolated from Malaysian V. roseus , showed weak cytotoxic activity against HCT 116 [ 89 ]. Furthermore, colchicine ( 41 ), isolated from the seeds of Gloriosa superba , demonstrated moderate activity against six human cancer cell lines (A549, MCF-7, MDA-MB231, PANC-1, HCT116, and SiHa) [ 90 ].…”
Section: Phytochemistry Of Ethiopian Anticancer Plantsmentioning
confidence: 99%
“…On the other hand, the monoterpenoid indole alkaloids vindoline and catharanthine, isolated from Malaysian V. roseus , showed weak cytotoxic activity against HCT 116 [ 89 ]. Furthermore, colchicine ( 41 ), isolated from the seeds of Gloriosa superba , demonstrated moderate activity against six human cancer cell lines (A549, MCF-7, MDA-MB231, PANC-1, HCT116, and SiHa) [ 90 ].…”
Section: Phytochemistry Of Ethiopian Anticancer Plantsmentioning
confidence: 99%
“…The main secondary metabolite is colchicine, which has anticancer activity but its toxicity profile is not acceptable. Several studies suggested the cytotoxic activity of semisynthetic derivatives of colchicine and thiocolchicoside; thus, the reported IC 50 values have no relevance to naturally occurring tropolones [ 133 , 134 , 135 , 136 ]. Gene expression, as well as cytotoxic effects of colchicine in human gastric cancer ASG and NCI-N87 cell lines, are evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Certain plant species can play a crucial role in blocking or activating transduction pathways in live cells by creating associated secondary metabolites with antimutagenic and cancer capabilities [ 64 ]. Some plant-derived anticancer drugs include vincristine [ 65 ], emodin [ 66 ], paclitaxel [ 67 ], kaempferol [ 68 ], linalool [ 69 ], colchicine [ 70 ], rutin [ 71 ], and quercetin [ 72 ]. Although the number of plant-derived anticancer compounds is vast, only a few have reached clinical use after successfully navigating the lengthy, expensive, and bureaucratic path from identification to cancer therapy effectiveness [ 64 ].…”
Section: Prospective Application Of Plant-based Materials In Cancer T...mentioning
confidence: 99%